Environmental Compensation of Large-scale Ventures in the State of Amazonas: relation between Biodiversity Conservation and Development - Reis, João Rodrigo Leitão dos; Faria, Ivani Ferreira de; Fraxe, Therezinha de Jesus Pinto (Sociedade & Natureza, 2017)
The negative social and environmental impacts of the super large-scale building ventures in Brazil areretributed through seven kinds of environmental compensation. A highlight of these is EnvironmentalCompensation - set forth in Federal Statute nº. 9.985/2000 (SNUC), Article 36, intended for conservationunits. An analysis about environmental compensation of large-scale enterprises in the state of Amazonasis presented in this particular article of the statute, done with exploratory surveying. It was discoveredthat the first Environmental Compensation in Amazonas is based on the former CONAMA Resolutionnº. 10/1987, applied to the Balbina electric power plant. After ten years of SNUC, R$ 23.341.294,65 wasraised and direct enforcement was done by the venture in the sum of R$ 216.466,63. The EnvironmentalCompensations originated from the Energy sector, including 19 conservation units. Around 24,36% ofthe Environmental Compensations has been applied in building infrastructure and aquiring equipmentand consumer goods. There are 15 enterprises using Environmental Compensation yet to be carried out.The conclusion is that technical, legal, and political factors limit environmental licensing affecting theEnvironmental Compensation which effectively need regulations and a more vigorous social control andtransparency.